SENGKETA ANGGOTA PARTAI POLITIK DALAM PENGUSUNGAN CALON BUPATI DIHUBUNGKAN DENGAN PUTUSAN PENGADILAN NEGERI INDRAMAYU NOMOR: 30/PDT.G/2015/PN.IDM - Abas, Suhendar (Yustitia, 2017)
The recent dispute of political party members is the Gerindra Party which nominates its members in the elections of Indramayu District Head 2015, but does not resort to a settlement mechanism through the Party Court in Gerindra as stipulated in Article 32 Paragraph (2) of Law Number 02 Year 2011 About the amendment of Law Number 02 Year 2008 on political parties.